2006
DOI: 10.2478/s11686-006-0039-z
|View full text |Cite
|
Sign up to set email alerts
|

Vitellocyte ultrastructure in the cestode Didymobothrium rudolphii (Monticelli, 1890): possible evidence for the recognition of divergent taxa within the Spathebothriidea

Abstract: In the spathebothriidean tapeworm Didymobothrium rudolphii (Monticelli, 1890) the fine structure of the vitellocytes at different stages of their development within the vitelline follicles, vitelline ducts and uterus was studied for the first time using transmission electron microscopy. The vitellocyte inclusions of D. rudolphii are shell globule clusters containing tightly packed shell globules associated with a matrix of moderate electron density, glycogen granules, large electron-lucent lipid droplets (up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 19 publications
4
38
1
Order By: Relevance
“…The general pattern of vitellogenesis in P. trygonis is similar to that in other lower cestodes, namely the pseudophyllideans (OEwiderski and Mokhtar 1974, Korneva 2001, Levron et al 2007, spathebothriideans Poddubnaya et al 2005Poddubnaya et al , 2006, tetraphyllideans (Mokhtar-Maamouri and OEwiderski 1976), nippotaeniids (Korneva 2002), gyrocotylids (Xylander 1987), amphilinids (Xylander 1988), caryophyllideans (Mackiewicz 1968, OEwiderski and Mackiewicz 1976, Poddubnaya et al 2003 and to two …”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The general pattern of vitellogenesis in P. trygonis is similar to that in other lower cestodes, namely the pseudophyllideans (OEwiderski and Mokhtar 1974, Korneva 2001, Levron et al 2007, spathebothriideans Poddubnaya et al 2005Poddubnaya et al , 2006, tetraphyllideans (Mokhtar-Maamouri and OEwiderski 1976), nippotaeniids (Korneva 2002), gyrocotylids (Xylander 1987), amphilinids (Xylander 1988), caryophyllideans (Mackiewicz 1968, OEwiderski and Mackiewicz 1976, Poddubnaya et al 2003 and to two …”
Section: Discussionmentioning
confidence: 71%
“…In P. trygonis, there are massive concentrations of lipids that, like those of G. erinaceus, and P. pastinacae, are of the saturated type. In four trypanorhynch species, the large numbers of lipid droplets were localised only in the vitellocyte cytoplasm, never inside the cell nuclei as reported in the tetraphyllidean Echeneibothrium beauchampi by Mokhtar-Maamouri and OEwiderski (1976) or the spathebothriidean Didymobothrium rudolphii by Poddubnaya et al (2006). Studies by Smirnov and Bogdan (1998) have shown that the degree of unsaturation of lipids between the pseudophyllideans Eubothrium crassum and Diphyllobothrium dendriticum was related to definitive host temperature.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Ultrastructural characters of the vitellarium might be useful .... for a better understanding of the relationships between different taxa within the neoophoran Platyhelminthes (Gremini & Falleni, 1998) including Cestoda (Świderski & Mackiewicz, 1976;Świderski & Xylander, 2000;Bruňanská et al, 2005;Poddubnaya et al, 2006Poddubnaya et al, , 2012Levron et al, 2007). The structure and composition of eggshell-forming globules in vitellocytes have been considered to be especially phylogenetically informative (Gremigni & Falleni, 1991;Falleni et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…To date, limited data are available on vitellogenesis in the Caryophyllidea, one of the basal groups of the Eucestoda. Out of about 150 species of four currently recognised families (Mackiewicz, 1994;Oros et al, 2008) seven members belonging to the two families (Caryophyllaeidae, Lytocestidae) were studied, namely Archigetes sieboldi (by Poddubnaya et al, 2003;Bruňanská et al, 2012b), Caryophyllaeus laticeps (Pallas, 1781) (by Ortner-Schönbach, 1913;Mackiewicz, 1968;Świderski et al, 2004a;Bruňan-ská et al 2010), Caryophyllaeides fennica (by Mackiewicz, 1968), Glaridacris catostomi (by Świderski & Mackiewicz, 1976), Wenyonia virilis (by Świderski et al, 2009), Atractolytocestus huronensis (by Bruňanská et al, 2009), Khawia armeniaca (by Świderski et al, 2004b) and Monobothrioides chalmersius (by Arafa 2012). As far as C. laticeps is concerned, the first histological and histochemical investigation on vitellogenesis was based on light microscopy (Mackiewicz, 1968), and supplemented by ultrastructural data in two brief abstracts (Świderski et al, 2004a(Świderski et al, , Bruňanská et al, 2010.…”
Section: Introductionmentioning
confidence: 99%